Bridging Sacred Traditions: Seyyed Hossein Nasr’s Hermeneutics and the Application of Biblical References in “The Study Quran” - Andesra, Aan; Alfabanni, Tunde Ahmed (Universitas Islam Tribakti Lirboyo Kediri, 2025)
The application of biblical references in the field of interpretation is not a new phenomenon, but it does not make it a common practice. This study examines Seyyed Hossein Nasr's construct of thought in The Study Quran (TSQ) in the application of the Bible as a reference for interpretation. This application did not arise from a vacuum, but was followed by certain constructive factors that led to the application of biblical references in the framework of The Study Quran. This study uses a qualitative-philosophical method by utilizing John Hick's Religious Inclusivism-Religious approach from John Hick (ultimate reality, inclusivism paradigm, and theocentric model) to highlight the theological dimension, as well as the Philosophical Hermeneutics from Hans-George Gadamer (historical influence, pre-understanding, and assimilation of horizons) in revealing the socio-historical dimension of Seyyed Hossein Nasr. The results of the study show that Seyyed Hossein Nasr assesses the Bible as a text with complex historical value, and that the involvement of the Bible in the realm of interpretation has the purpose of expanding the meaning of the verses of the Qur'an. Given the issue of distortion, this work emphasizes the aspect of distortion of meaning and interpretation rather than distortion of the text. The view of distortion indirectly imposes limitations by placing the Bible as a historical text limited to the functions of historical contextualization and intertextual analysis. In the theological dimension, Seyyed Hossein Nasr's position is inclusive, while in the hermeneutical-philosophical perspective, it shows a hermeneutic situation with intellectual traces and contemporary dynamics, including the 9/11 phenomenon that gave rise to Islamophobia in New York. Given the limitations of the Eastern school in assessing the application of the Bible as presented and the dynamics of the Western school, which is open to cross-traditional references, supported by the 9/11 phenomenon, this shows an effort to bridge two different traditions in the realm of interpretation. Contribution: This study theoretically contributes by integrating John Hick’s religious inclusivism and Gadamer’s philosophical hermeneutics to construct an interreligious interpretive framework that explains Seyyed Hossein Nasr’s inclusive use of biblical references in The Study Quran.